Characteristics of Crime in the City Municipality of Maribor - Meško, Gorazd; Hacin, Rok (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The article focuses on trends and characteristics of crime in the City Municipality of Maribor. Based on data on crime and population, crime trends in the Municipality of Maribor and at the national level were determined in the period 2000–2024. The number of crimes, crime rates and crime indexes were analysed. On average, crime in the Municipality of Maribor represented 7.6% of all crimes in the Republic of Slovenia. A comparison of crime trends in the City Municipality of Maribor and Slovenia showed differences in crime trends in the period 2000–2024. An analysis of individual groups of crimes showed that in the City Municipality of Maribor, compared to the national level, the volume of property, violent and sexual crime, as well as crime related to illegal drugs, is higher. The findings highlighted the role of factors in the local environment on characteristics of crime.